PENGARUH SIKAP TERHADAP FREE TRIAL DAN PRICE DISCOUNT TERHADAP INTENSITAS MENDAFTAR DENGAN MODERASI BRAND IMAGE - Anggraeni, Dewi; Rahmat Syah, Tantri Yanuar (Lembaga Penerbitan Unversitas Esa Unggul, 2017)
The current early childhood education is growth, parents is having a choice to send their children, very competitive offer, many school available likes religious schools and montessori school. Montessori school for other people now most famous but in the fact for regional in Kelapa Dua Tangerang Enrollment intention is very low diffrent to the other markets area, they have a wrong perception and they think montessori school lis non - moeslim religious school, the socialization make strategy free trial promotion, price discount to up Enrollment intention. Purpose this riset of this study to looking for to analyze whether the prospective parents' attitude towards free trial and a price discount, whether affect ting the intention to enrollment and whether the brand image school can support of the promotion strategy. Methods of data analysis using multiple linear regression method. The results showed that there are significant attitude towards free trial to the intention to register, while attitudes toward discounted price does not affect the intention to register, there is no moderating influence of brand image on the relationship attitude towards free trial and discount price to the intention to register. Price discounts are offered at a school can not guarantee the quality of the schoolbut the good image that school will be a major factor for choosing a school with socialization school through free trial. Keywords: free trial, price discount, brand image, intention